Computer search for graceful labeling: a survey - Ljiljana Brankovic; Michael J. Reynolds (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2022)
This paper surveys the main computer search results for finding graceful labeling of trees. The paper is devoted to the memory of Mirka Miller, who made an outstanding contribution to the area of graph labeling.